Design, analysis and fabrication of robotic arm for sorting of multi-materials - Khoo, Zern Yi (Universiti Malaysia Perlis (UniMAP), 2016)
This paper presents about design, analyses development and fabrication of robotic arm for sorting multi-material. The major problem that urges the initiation of the project is the fact that manufacturing industry is growing at relatively faster rate. Most of the company produce high load robotic arm. Less company create light weight, and affordable robotic arm. As the result, light weight and affordable robot is develop to cover this issue. Plastic materials was used to construct the body of robotic arm, and an optical sensor was implemented to provide basic recognition of object to be carried. The robotic arm used five servomotors for overall operation; four for its joints, and one for the gripping mechanism. The gripper was designed and fabricated using Perspex due to the light weight and high strength of the material. The operation of the robotic arm was governed by Basic Stamp programming sequence and the device was expected to differentiate material and other objects based on reflective theory, and perform subsequent operations afterwards. The SolidWorks was used to model the detail design the robotic arm, and to stimulate the motion of the device.